Case report: Hyperactive delirium after a single dose of zolpidem administered additionally to psychopharmacotherapy including clozapine - Preiss, Maximilian; Rabl, Ulrich; Popper, Valentin; Watzal, Victoria; Treiber, Michael; Ivkic, Dominik; Praschak-Rieder, Nicole; Naderi-Heiden, Angela; Fugger, Gernot; Frey, Richard; Rujescu, Dan; Bartova, Lucie (Frontiers in Psychiatry, 2023)
The non-benzodiazepine hypnotic zolpidem is frequently administered as a short term psychopharmacotherapy for insomnia. Although it is well established in a broad clinical routine and often well tolerated, severe delirium and complex sleep behavior were reported in rare cases. Hereby, it remains unclear whether zolpidem´s potential for delirium might be enhanced when combined with further psychopharmacotherapeutics. The present case report portrays a young male Caucasian inpatient with schizoaffective disorder, who was admitted due to severe hyperactive delirium after a single dose of zolpidem 10 mg that was administered in addition to already established psychopharmacotherapy including clozapine 200 mg/day, aripiprazole 15 mg/day and cariprazine 4.5 mg/day. In detail, disorientation, agitation, confabulations, bizarre behavior, and anterograde amnesia occurred shortly after ingestion of zolpidem and gained in intensity within a couple of hours. Once zolpidem was discontinued, the abovementioned symptoms subsided completely and did not reoccur. Since a clear temporal association could be drawn between the intake of zolpidem and the onset of hyperactive delirium, the present clinical experience should serve as a cautionary note for combining potent sedative-hypnotics and substances with anticholinergic properties, even in young adults in a good general condition. Moreover, our case argues for the necessity of further research into the pathomechanism of the interaction potential of non-benzodiazepines as zolpidem, especially with substances exerting anticholinergic properties, which are known for their potential to precipitate delirium. Therefore, the metabolic pathways of the concurrently administered substances should be further taken into account.